742. "Troponin Leaks" in Patients with Acute Respiratory Viral Infections Enrolled in SUPERNOVA: A Marker of Worse Clinical Outcomes. (26th November 2018) - Ruiz, Ernesto; Lengi, Bashir; Gray, Tiffany; Mushtaq, Mahwish; Musher, Daniel; Rodriguez-Barradas, Maria
Abstract: Background: Cardiac troponin I (cTnI) is a specific marker of cardiac muscular injury. Many patients hospitalized with acute respiratory illness (ARI) have elevated cTnI levels but do not meet EKG criteria for an acute ischemic cardiac event. Troponin leaks could be due to demand ischemia or acute inflammation of the myocardium. We hypothesized that patients with viral ARI and elevated cTnI have worse cardiopulmonary outcomes than those with viral ARI and normal cTnI. Methods: From November 11, 2016–September 30, 2017 nasopharyngeal swabs from patients enrolled in SUPERNOVA ARI Study, a CDC/2-VA site, active surveillance platform to evaluate the incidence of viral infection in patients hospitalized with symptoms and/or signs of ARI, were tested using a FilmArray Respiratory Panel. Based on detection of any virus, patients were categorized as positive (vPCR+) or negative (vPCR−). Patient enrolled at the Houston site with cTnI obtained <48 hours of admission were included in the analysis. cTnI above upper limit of normal (>0.03 ng/dL) was defined as elevated. Demographic and clinical data were abstracted from chart review. Outcomes were myocardial infarction (MI) on admission, 30- and 90-day re-admissions due to cardio-respiratory illness and 30- and 90-day all-cause mortality. For the univariable analysis of baseline factors and outcomes we used unpaired t -tests for continuous variables and χ 2 or Fisher exact test for categorical variables as appropriate. Results: Ninety-four of 332 cases were vPCR positive and cTnI levels on admission were available in 86. Demographics and comorbidities were all similar for the high ( N = 42) and normal ( N = 44) cTnI groups. Compared with normal cTnI group, those with high cTnI had similar 30- and 90-day readmission rates (14% vs. 9%, P = 0.4 and 26% vs. 16%, respectively, P = 0.2). However, 30- and 90-day mortality rates were higher for high cTnI patients (10% vs. 0% and 19% vs. 5%, P < 0.03). Conclusion: Troponin elevation on patients with a documented viral respiratory infection is associated with higher 30- and 90-day mortality rates. Troponin leaks should not be dismissed as a trivial finding in this group of patients. Further work on its pathogenesis is warranted. Disclosures: All authors: No reported disclosures.